Peran Pondok Pesantren dalam Meningkatkan Mutu Pendidikan Agama Islam di Sekolah - Latifah Latifah (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2020)
The existence of the Krapyak Islamic Boarding School as a sub-culture of the Islamic community of Krapyak has become a distinct feature for the people of Krapyak. When viewed from a sociological perspective, Islamic pesantren culture contributes to determining certain value standards in society as a social system. This study seeks to see the role played by the Krapyak Islamic Boarding School for improving the quality of Islamic Religious Education at SDN Jageran Krapyak. The research findings show that Krapyak Islamic Boarding School plays a role for improving the quality of Islamic Education in SDN Jageran at least through understanding the material, forms of cooperation, and the results of quality improvement in the aspects of cognitive, affective and psychomotor. Keywords: Krapyak Islamic Boarding School, social system, social structure, Education Quality Development Intisari Keberadaan pondok Pesantren Krapyak sebagai sub kultur masyarakat krapyak yang islami menjadi ciri tersendiri bagi masyarakat krapyak. Bila dilihat dari perspektif Sosiologi, kultur islami pesantren turut andil dalam menentukan standar nilai tertentu dalam masyarakat sebagai sistem sosial.. Penelitian ini berusaha melihat peran yang dimainkan oleh Pondok Pesantren Krapyak terhadap peningkatan mutu Pendidikan Agama Islam (PAI) di SDN Jageran Krapyak. Temuan penelitian menunjukkan bahwa Pondok Pesantren Krapyak berperan dalam meningkatkan mutu PAI di SDN jageran setidaknya melalui pemahaman materi, bentuk kerjasama dan hasil peningkatan mutu dalam aspek kognitif, afektif dan psikomotorik. Kata Kunci: Pondok Pesantren Krapyak, sistem sosial, struktur sosial, Peningkatan Mutu Pendidikan